PPP Exchange-Rate Rules and Macroeconomic Stability - Dornbusch, Rudiger (Journal of Political Economy, 1982)
Exchange-rate rules that link exchange depreciation to domestic price-level changes are shown to affect the output price-level stability trade-off through two separate channels. On one hand a PPP-oriented exchange-rate policy tends to maintain constant the real exchange rate, thus stabilizing demand. But the exchange-rate policy works also through the supply side, via the prices of imported intermediate goods. Here exchange-rate indexation works to amplify the effect of wage disturbances on prices and potentially on output. In the context of a rational-expectations model with long-term overlapping wage contracts, the analysis shows that the impact of increased indexation on output and price-level stability depends on the extent of monetary accommodation.